Quantitative Trait Locus Analysis of Seed Germination and Seedling Vigor in Brassica rapa Reveals QTL Hotspots and Epistatic Interactions - Basnet, Ram K.; Duwal, Anita; Tiwari, Dev N.; Xiao, Dong; Monakhos, Sokrat; Bucher, Johan; Visser, Richard G. F.; Groot, Steven P. C.; Bonnema, Guusje; Maliepaard, Chris (Frontiers in Plant Science, 2015)
The genetic basis of seed germination and seedling vigour is largely unknown in Brassica species. We performed a study to evaluate the genetic basis of these important traits in a B. rapa doubled haploid population from a cross of a yellow-seeded oil-type yellow sarson and a black-seeded vegetable-type pak choi. We identified 26 QTL regions across all 10 linkage groups for traits related to seed weight, seed germination and seedling vigour under non-stress and salt stress conditions illustrating the polygenic nature of these traits. QTLs for multiple traits co-localized and we identified eight hotspots for quantitative trait loci (QTL) of seed weight, seed germination, and root and shoot lengths. A QTL hotspot for seed germination on A02 mapped at the B. rapa FLOWERING LOCUS C (BrFLC2). Another hotspot on A05 with salt stress specific QTLs co-located with the B. rapa FATTY ACID DESATURASE 2 (BrFAD2) locus. Epistatic interactions were observed between QTL hotspots for seed germination on A02 and A10 and with a salt tolerance QTL on A05. These results contribute to the understanding of the genetics of seed quality and seeding vigour in B. rapa and can offer tools for Brassica breeding.